Pengembangan E-Modul Matematika Berbasis Etnomatematika Tanimbar - Batkunde, Yoseph; Nifanngelyau, Jakobus (Mandalika Mathematics and Educations Journal, 2024)
The purpose of this study was to develop a Tanimbar ethnomathematics-based mathematics learning module. The sample used in this study amounted to 31 people consists of 7 students and 1 teacher for small group try outs and 20 students and 3 teachers for try outs in learning. The instruments and data collection techniques used in this study were questionnaires, observations, tests, and interviews to obtain data on the quality of teaching material products in the form of Tanimbar ethnomathematics-based mathematics e-modules obtained during the e-Module try out. The data analysis technique uses a quantitative approach, input, responses, criticism and suggestions for improvement through questionnaires and the results of the learning outcomes achievement test, while qualitative data is obtained from observations and interviews on the use of Tanimbar ethnomathematics-based mathematics e-Modules. The final conclusion shows that the development of Tanimbar Ethnomathematics-based Mathematics E-Modules is very valid and feasible to use for junior high school student’s learning with a percentage of 91.7% and obtaining try out results in learning with an average value of student completeness on PB1 and PB2 is 88.5% with a very good category.